Recent Advances in the Controlled Release of Growth Factors and Cytokines for Improving Cutaneous Wound Healing - Nurkesh, Ayan; Jaguparov, Alexandr; Jimi, Shiro; Saparov, Arman (Frontiers in Cell and Developmental Biology, 2020)
Bioengineered materials are widely utilized due to their biocompatibility and degradability, as well as their moisturizing and antibacterial properties. One field of their application in medicine is to treat wounds by promoting tissue regeneration and improving wound healing. In addition to creating a physical and chemical barrier against primary infection, the mechanical stability of the porous structure of biomaterials provides an extracellular matrix-like niche for cells. Growth factors and cytokines, which are secreted by the cells, are essential parts of the complex process of tissue regeneration and wound healing. There are several clinically approved growth factors for topical administration and direct injections. However, the limited time of bioactivity at the wound site often requires repeated drug administration that increases cost and may cause adverse side effects. The tissue regeneration promoting factors incorporated into the materials have significantly enhanced wound healing in comparison to bolus drug treatment. Biomaterials protect the cargos from protease degradation and provide sustainable drug delivery for an extended period of time. This prolonged drug bioactivity lowered the dosage, eliminated the need for repeated administration, and decreased the potential of undesirable side effects. In the following mini-review, recent advances in the field of single and combinatorial delivery of growth factors and cytokines for treating cutaneous wound healing will be discussed.